Identification of Possible Biomarkers in Cardiovascular Diseases - Coculescu, Bogdan-Ioan; Dincă, Gabi Valeriu; Manole, Gheorghe; Coculescu, Elena Claudia (Journal of Hematology Research, 2022)
Currently, one of the major medical topics researched is the identification in the most diverse diseases, of new molecular biomarkers that would allow the establishment of a positive diagnosis, but also of the response to a certain established treatment (risk biomarkers). Prolonging the lifespan of individuals and increasing the frequency of heart failure from 1-2% in the adult population, regardless of age, to 10-12% in people over 70 explains the worldwide interest in identifying biomarkers and in this condition, regardless of etiology, which offers the possibility of complex assessment of the condition, including the prognosis.